Late-Onset Wilson's Disease - Žigrai, Miroslav; Vyskočil, Milan; Tóthová, Andrea; Vereš, Peter; Bluska, Peter; Valkovič, Peter (Frontiers in Medicine, 2020)
Wilson’s disease is a rare autosomal recessive disease, caused by impaired secretion of copper into bile due to a defective function of the ATPase 7B enzyme. Clinical manifestation is predominantly hepatic and neurological. Wilson’s disease is traditionally considered a disease of children and young adults. It rarely manifests after 40 years of age. In our case report, we present a 67 year old female in whom Wilson’s disease manifested as tremors of the upper extremities and chin that were originally assessed as part of cerebral atherosclerosis and Parkinson’s disease. Only the histological finding of liver steatofibrosis, performed due to suspected metastatic changes of the liver, led in the context of neurological symptoms to correct diagnosis and successful treatment.